Growth Kinetics of Laves Phase and Its Effect on Creep Rupture Behavior in 9Cr Heat Resistant Steel - XIA, Zhi-xin; WANG, Chuan-yang; LEI, Chen; LAL, Yun-ting; ZHAO, Yan-fen; ZHANG, Lu (Journal of iron and steel research, international, 2016)
The effects of Laves phase formation and growth on creep rupture behaviors of P92 steel at 883 K were studied.The microstructural evolution was characterized using scanning electron microscopy and transmission electron microscopy.Kinetic modeling was carried out using the software DICTRA.The results indicated Fe_2（W,Mo）Laves phase has formed during creep with 200 MPa applied stress at 883 Kfor 243 h.The experimental results showed a good agreement with thermodynamic calculations.The plastic deformation of laths is the main reason of creep rupture under the applied stress beyond 160 MPa,whereas,creep voids initiated by coarser Laves phase play an effective role in creep rupture under the applied stress lower than 160 MPa.Laves phase particles with the mean size of 243 nm lead to the change of creep rupture feature.Microstructures at the vicinity of fracture surface,the gage portion and the threaded ends of creep rupture specimens were also observed,indicating that creep tensile stress enhances the coarsening of Laves phase.